Skeletal Muscle-Released Extracellular Vesicles: State of the Art - Rome, Sophie; Forterre, Alexis; Mizgier, Maria Luisa; Bouzakri, Karim (Frontiers in Physiology, 2019)
All cells export part of their intracellular content into the extracellular space through the release of various types of Extracellular Vesicles (EVs). They are synthetized either from the budding of the plasma membrane (i.e.; microparticles (MP, 150-300nm size)) or from the late endosomes in which intraluminal vesicles progressively (ILVs) accumulate during their maturation into multivesicular bodies (MVBs). ILVs are then released into the extracellular space through MVB fusion with the plasma membrane (i.e.; exosomes (50-100nm size)). In the context of metabolic diseases, recent data have highlighted the role of EVs in inflammation associated with pancreas dysfunction, adipose tissue homeostasis, liver steatosis, inflammation and Skeletal Muscle (SkM) insulin-resistance (IR). Among these insulin-sensitive tissues, SkM is the largest organ in human and is responsible for whole-body glucose disposal and locomotion. Therefore, understanding the contribution of SkM-EVs in the development of diabetes/obesity/dystrophy/sedentarity-related diseases is a hot topic. In this review we have summerized the role of SkM-EVs in muscle physiology and in the development of metabolic diseases and identify important gaps that have to be filled in order to have more precise informations on SkM-EVs biological actions and to understand the functions of the different subpopulations of SkM-EVs on the whole body homeostasis